1996
DOI: 10.1007/bf00785759
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of mania: time trends in relation to gender and ethnicity

Abstract: In order to investigate conflicting reports about possible changes in the incidence of mania, we established first contact rates for mania in the defined area of Camberwell between 1965 and 1984. There was some evidence for an increase in the first contact rate of mania, especially in females. This rise may be associated with the influx into Camberwell of individuals of Afro-Caribbean origin who showed significantly higher rates than the white group [adjusted rate ratio 3.1; 95% confidence interval (CI) 1.4-6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…With respect to RDC diagnoses, the case register for Camberwell, the local catchment area of the Maudsley Hospital, has been used to ascertain first-contact patients between 1965 and 1984 with nonaffective psychoses, mania, or hypomania. 25,26 Two twins (0.45%) from our present sample were among the 445 individuals from Camberwell who received an RDC diagnosis of psychosis. This was within the confidence interval (CI) for the estimate of 1.15% (95% CI, 0.16-2.14) same-sex twins with a co-twin surviving to 15 years of age (calculated from Maudsley Twin Register data).…”
Section: Statistical Analysis Twin Methods Issuesmentioning
confidence: 99%
“…With respect to RDC diagnoses, the case register for Camberwell, the local catchment area of the Maudsley Hospital, has been used to ascertain first-contact patients between 1965 and 1984 with nonaffective psychoses, mania, or hypomania. 25,26 Two twins (0.45%) from our present sample were among the 445 individuals from Camberwell who received an RDC diagnosis of psychosis. This was within the confidence interval (CI) for the estimate of 1.15% (95% CI, 0.16-2.14) same-sex twins with a co-twin surviving to 15 years of age (calculated from Maudsley Twin Register data).…”
Section: Statistical Analysis Twin Methods Issuesmentioning
confidence: 99%
“…A middle syndrome between this and schizophrenia (schizomania) has also been reported as more common. 20 Furthermore, Selten and colleagues 14 demonstrated an increase in all psychotic disorders in Caribbean migrants to the Netherlands. Selten and colleagues 21 also examined the admission rates for both first-episode bipolar disorder of manic and depressed types in migrant groups in the Netherlands and found only small increases in the admission rates for manic illness in Surinamese, but not Turkish, migrants.…”
Section: Are the Rates Of Other Psychoses Raised?mentioning
confidence: 99%
“…Epidemiologic studies have suggested a disparity in rates of mania among specific ethnic groups, [9][10][11][12][13][14][15][16] but immigrant status has generally not been examined in these analyses. The limited clinical data that are available on the effect of immigrant status on presence of BD has yielded inconclusive results, with one report of manic subjects being significantly more likely to be foreign-born than subjects with schizophrenia in a small sample of inpatients from McLean Hospital.…”
mentioning
confidence: 99%